Cardiometabolic dysfunction burden and mortality outcomes in metabolic dysfunction-associated steatotic liver disease - Ying Wen; Yu Min; Yi Lei; Zhigong Wei (PLoS ONE, 2025)
Background/Objectives The term metabolic dysfunction-associated steatotic liver disease (MASLD) reflects the key role of cardiometabolic dysfunction in steatotic liver disease. We aim to assess the association between cardiometabolic dysfunction burden and mortality outcomes in MASLD. Methods Participants with MASLD were selected from the National Health and Nutrition Examination Survey (NHANES) database between 1999 and 2018. The mortality outcomes of participants with different numbers of cardiometabolic risk factors were compared by using Kaplan-Meier curves and Cox regression analysis. Results This study included 9,017 participants with MASLD (4,613 men and 4,404 women, median age 49.0). With a median 115-month follow-up, 1,447 all-cause deaths and 407 cardiovascular-specific deaths were observed. Multivariate regression analysis showed that participants with five cardiometabolic risk factors had significantly increased all-cause mortality risk compared to those with one risk factor (adjusted hazard ratio [aHR] = 3.57, 95% confidence interval [CI]: 2.04–6.24, P < 0.001). Similarly, the cardiovascular mortality risk was markedly higher for participants with five risk factors (aHR = 7.72, 95% CI: 1.89–31.53, P = 0.004). Among participants with the same number of cardiometabolic risk factors, those with blood glucose or blood pressure abnormalities showed the lowest survival rates than other subgroups. Besides, participants with younger ages were more vulnerable to the harmful prognostic effects of cardiometabolic dysfunction burden on the mortality risks. Conclusions The MASLD population with high cardiometabolic dysfunction burdens exhibits increased mortality risk. Assessing cardiometabolic dysfunction, particularly abnormalities in blood glucose and blood pressure, is crucial for effective management in this population.